Bagaimana Persepsi Masyarakat Lokal Terhadap Wilayah Yang Dilindungi Di Pulau Pahawang? - Velda Reissa Valeska; Indra Gumay Febryano; Yulia Rahma Fitriana; Samsul Bakri (Journal of Tropical Marine Science, 2022)
This study aims to analyse how the community's perception of protected areas on small islands. Data was collected by interview by questionnaire and observation. The collected data is then analysed using a Likert Scale to measure public perception of the areas, institutions, and tourism potential from areas protected by the community. The results showed that the community's perception of the existence of the protected area was classified high. The area is located on the top of the highest hill on Pahawang Island. The community protects it because there is a sacred site and the forest vegetation around it is still well preserved. In addition, the community realizes that the forest is very important as a water reserve and prevents erosion, but has not been used optimally economically. Perception of the institution is classified high, and it is found that the community is fond of the institution. The community already has an informal agreement to protect and not open the area. This agreement has been obeyed by the community until now, so that the sustainability of the forest is still maintained. The protected area can be used potentially for religious tourism, where the results of public perception is very good. The village government needs to plan good religious tourism also and improvement of facilities and infrastructure, so that the management of this area can improve the welfare of the community and the conservation function is maintained.